A Dyadic Exploration of Marital Satisfaction as a Mediator between Religiosity and Depressive Symptoms. Issue 3 (3rd April 2021) - Rose, Andrew H.; Anderson, Shayne R.; Miller, Richard B.; Marks, Loren D.; Hatch, Trevan G.; Card, Noel A.
Abstract: Substantial research has established that religiosity can be a protective factor against depression. However, little research has explored these associations within couples. Theory and previous research provide evidence that these relations may be manifest through marital satisfaction. A longitudinal Actor–Partner Interdependence Model was used to test the dyadic relations between religiosity at Time-3, marital satisfaction at Time-4, and depressive symptoms at Time-5 in a long-term committed community sample of 331 married couples. Husbands' religiosity had a direct positive longitudinal impact on husbands' marital satisfaction 1 year later. Husbands' religiosity led to lower levels of their own depressive symptoms through the indirect effects of husbands' and wives' marital satisfaction. Wives' religiosity did not significantly impact any of the variables in the study.